The Representation of Indonesian Women Migrant Workers in the Lyric of Tarling Ndremayon - Haira Rizka (Masyarakat Linguistik Indonesia Universitas Andalas, 2020)
This research aims to: (1) identify the semantic meaning of Tarling Ndremayon lyric, representing, representing the life of TKW, and (2) social factors that trigger TKW's life representation in the Tarling Ndremayon songs. The subjects of this research were six Tarling Ndremayon songs. The data were collected through a note-taking technique and interview. The collected data were then analyzed by employing textual analysis. The research findings show that Tarling Ndremayon lyrics that represent the life of TKW narrate five semantic meanings, such as affliction, sacrifice, loneliness, poverty, and jealousy. It implies that the women migrant workers and their families suffer from their condition since the lyrics' major semantic meanings narrate sadness. Meanwhile, the social factors that represent TKW's life in the Tarling Ndremayon songs are economy, affection, and education. The singers presented these representations: the women migrant worker, her husband, and her child.